P-32 Supportive care of oral mucositis in haematology patients: service evaluation and improvement project. (1st March 2017) - MacDermott, Claire Nicola; Davies, James; Thomas, Cannon; Fingas, Sam
Abstract : In haematological malignancy high dose chemotherapy or bone marrow transplant commonly cause oropharyngeal mucositis. At Sheffield Teaching Hospitals NHS Foundation Trust (STH) there is joint working between palliative care (PCT) and haematology to manage these patients. The aim was to evaluate the service, implement improvements and re-evaluate. Initial evaluation was performed against the STH Standard Operating Procedures (SOP) for haematology patients suffering with mucositis and referred to PCT. Convenience sampling was used and data collected between April-October 2015. Case notes of 19 patients referred to PCT with mucositis were reviewed. The SOP recommends referral to PCT if third line interventions fail. The results of the initial evaluation showed that most patients, 18 and 17 patients respectively, had antacid-oxceitacaine and lidocaine mouthwashes prescribed. Only 1 (5%) had the treatment fully optimised; i.e. alternating four hourly and to swallow. Fifteen patients (79%) were referred to PCT before completing third line treatment without systemic treatment with opioid being initiated. Intervention: An education programme and simple flowchart for prescribing was developed with a new SOP. Final evaluation was performed on the next 11 sequential haematology patients with mucositis from February-April 2016. All patients had the mouthwashes prescribed with appropriate frequency and route. Six patients required systemic PRN or regular opioids. Four patients (67%) had PRN opioids prescribed appropriately. All transdermal patches (buprenorphine or fentanyl) were prescribed and titrated appropriately. One patient (9%) was referred to PCT team earlier than the flowchart recommended compared to 79% previously. A survey of staff reported increased confidence with prescribing and improvement in patient experience, with PCT only reviewing those with specialist needs. Conclusion: This service evaluation and improvement project has enhanced prescribing and the confidence of haematology team in managing those with mucositis.